2022
DOI: 10.1186/s12879-022-07382-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and drug sensitivity of pathogenic bacteria in diabetic foot ulcer patients with necrotizing fasciitis at a diabetic foot center in China

Abstract: Background Diabetic foot ulcer is one of the major complications for patients with diabetes, and has become an important cause of non-traumatic amputation. Necrotizing fasciitis is a life-threatening soft-tissue infection involving the fascia and subcutaneous tissue. When diabetic foot ulcers are complicated by necrotizing fasciitis (DNF), this increases the risk for amputation and mortality, making DNF treatment more complicated, and eventually leading to amputation and mortality. However, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Methicillin-resistant Staphylococcus aureus (MRSA, Gram-positive), Pseudomonas aeruginosa ( P. aeruginosa , Gram-negative), and E. coli are the most common pathogens of infected wounds and have been chosen to be evaluated for in vitro antibacterial susceptibility against LM2-RMR 0–50% and LM2-R 0–50% hydrogels using an agar disk diffusion method. As shown in Figure E, Figure S12, and Figure S13, the obvious inhibition halos were observed after being incubated with LM2-RMR 1%‑50% hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA, Gram-positive), Pseudomonas aeruginosa ( P. aeruginosa , Gram-negative), and E. coli are the most common pathogens of infected wounds and have been chosen to be evaluated for in vitro antibacterial susceptibility against LM2-RMR 0–50% and LM2-R 0–50% hydrogels using an agar disk diffusion method. As shown in Figure E, Figure S12, and Figure S13, the obvious inhibition halos were observed after being incubated with LM2-RMR 1%‑50% hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…There have been few reports of CR-PPE infection cases in China. 16 However, the resistance genes and plasmids of CR-PPE infection cases have not been studied. To the best of our knowledge, pWF127-NDM is the first report of a carbapenem-resistant plasmid containing bla NDM-1 in P. penneri in China.…”
Section: Resultsmentioning
confidence: 99%
“…E. faecalis is one of the most common bacteria cultured from all types of wounds and the third most common pathogen isolated from surgical site infections [ 18 , 19 ]. A retrospective study, which explored the distribution of pathogenic bacteria and drug susceptibility in 101 patients with DFUs complicated by necrotizing fasciitis, reported that E. faecalis was isolated from 18.5% of the total population enrolled and from 30% of all gram-positive bacteria [ 20 ]. All isolated strains were susceptible to nitrofurantoin, linezolid, daptomycin, teicoplanin, tigecycline, vancomycin and daptomycin.…”
Section: Discussionmentioning
confidence: 99%